2003
DOI: 10.1109/tasc.2003.812057
|View full text |Cite
|
Sign up to set email alerts
|

Critical current limiting factors in post annealed (Bi; Pb)/sub 2/Sr/sub 2/Ca/sub 2/Cu/sub 3/O/sub x/ tapes

Abstract: Abstract-Processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In fact, the value of 0.11 is the smallest 2212 SQUID index that we have measured for 2223 samples from a variety of sources. 2,10,20 J c was enhanced by reduction of cross-section area and by improved connectivity. OP processing reduced porosity and cracking from ϳ20% of the cross-section area in the FHT and FHTϩ1b samples to less than 5% in the FHT ϩOP sample, which proportionally enhanced the active cross-section area that carried current.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…In fact, the value of 0.11 is the smallest 2212 SQUID index that we have measured for 2223 samples from a variety of sources. 2,10,20 J c was enhanced by reduction of cross-section area and by improved connectivity. OP processing reduced porosity and cracking from ϳ20% of the cross-section area in the FHT and FHTϩ1b samples to less than 5% in the FHT ϩOP sample, which proportionally enhanced the active cross-section area that carried current.…”
mentioning
confidence: 97%
“…This as-rolled tape subsequently goes through a thermomechanical cycle that consists of a first heat treatment ͑HT1͒, an intermediate rolling ͑IR͒, and a final heat treatment ͑FHT͒. The FHT includes a second heat treatment ͑HT2͒ and a separate low temperature ''post anneal'' ͑PA͒ or a heat treatment combining HT2 and PA. 9,10 About 80% of the precursor oxide powder reacts to 2223 phase in HT1. IR helps densify the superconducting filaments while HT2 and any FHT further increase 2223 formation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The connectivity contribution to is not easy to define, though detailed magneto-optical current reconstructions are making this parameter much clearer [11]. In recent work, it has been shown that minimization of 2212 intergrowths is very valuable in raising (0 T, 77 K) and (0.1 T, 77 K), probably because such intergrowths strongly reduce the current path cross-section at 77 K [4]- [6]. However, 2212 intergrowths are only one of many current-limiting mechanisms controlling the of Bi-2223 tapes.…”
Section: Introductionmentioning
confidence: 99%